Heavy metal accumulation in plant species indigenous to a contaminated portuguese site: prospects for phytoremediation - Moreira, Helena (2012)
Phytoremediation is a promising alternative to conventional soil clean-up methods; however, up to date, there is still not enough information on plant species suitable for application in this field of science. Therefore, plant screening on contaminated sites can lead to the identification of further species of interest. In the present study, pedological and botanical characteristics of an industrialised area known for its metal contamination, in special with Zn—Esteiro de Estarreja, in Portugal—were examined in a 1-year screening. Twenty-seven species were found, with a higher occurrence and variability in the summer/spring season. Zinc levels in the tissues of the collected plant samples ranged from 34 mg kg−1 in shoots to 2,440 mg kg−1 in roots of different species. Species as Verbascum virgatum, Hypochoeris radicata, Phalaris arundinacea, Conyza bilbaoana, Paspalum urvillei and Aster squamatus have shown high Zn shoot accumulation and bioconcentration factors (BCFshoots > 1) and high metal translocation factors (TF > 1). Others, namely Spergularia capillacea, excluded Zn from the shoot tissues and stored the metal at the root zone (BCFroots > 1), behaving as tolerant plants. Plants were also screened for arbuscular mycorrhizal fungi colonisation, and only few species showed mycorrhizal presence, namely C. bilbaoana, Hirschfeldia incana, Epilobium tetragonum, Conyza sumatrensis, Pteridium aquilinum, P. urvillei and A. squamatus. The present work showed important indigenous species that can cope with installed harsh conditions and with potential for utilisation in phytoremediation strategies, either through metal removal to aerial parts or through its immobilisation in the root zone.